Integrating an Extended-Gate Field-Effect Transistor in Microfluidic Chips for Potentiometric Detection of Creatinine in Urine - Dhaniella Cristhina De Brito Oliveira; Fernando Henrique Marques Costa; Renato Massaroto Beraldo; José Alberto Fracassi da Silva; José Alexandre Diniz (Sensors)
Monitoring creatinine levels in urine helps to recognize kidney dysfunction. In this research, we developed a photocurable membrane for the detection of serum creatinine. Using a system based on field-effect transistors, we carried out creatinine quantification in synthetic urine. The device was able to cover values between 3 and 27 mmol L−1. The current sensitivity was 0.8529 (mA)1/2 mmol−1 L with 91.8% linearity, with the LOD and LOQ being 5.3 and 17.5 mmol L−1, respectively. The voltage sensitivity was 0.71 mV mmol−1 L with a linearity of 96.2%, with the LOD and LOQ being 4.2 and 14.0 mmol L−1, respectively. These data were obtained under flow conditions. The system performed very well during the measurements, with a hysteresis of about 1.1%. Up to 90 days after manufacture, the sensor still maintained more than 70% of its initial response. Even when used periodically during the first week and then stored unused at −18 °C, it was able to maintain 96.7% of its initial response. The device used in the flow setup only had a useful life of three days due to membrane saturation, which was not reversible. In the interference test, the membrane was also shown to respond to the urea molecule, but in a different response window, which allowed us to discriminate urea in synthetic urine. EGFETs can be used to identify variations in the creatinine concentration in urine and can help in therapeutic decision-making.